[RETRACTED] Efektivitas Pendekatan TPACK dalam Pembelajaran PAI untuk Meningkatkan Literasi Digital Siswa di SMKN 1 Pancung soal - Rika Sarmiko (Jurnal Pendidikan Tuntas, 2024)
After a rigorous, careful, and thorough review of the article published in the Jurnal Pendidikan Tuntas titled “The Effectiveness of the TPACK Approach in PAI Learning to Improve Students' Digital Literacy at SMKN 1 Pancung soal” Vol. 2, No. 4, December edition, pp. 573–582, 2024. This article was found to violate the publication principles of the Journal of Comprehensive Education and has been retracted. The article contains duplicate content. The editor conducted an investigation and found that an article with the same title was published in the Journal pendidikan tuntas, Vol. 2, No. 4, pp. 683–689, 2024, https://publikasi.abidan.org/index.php/jpt/article/view/947/693. The document and its contents have been removed from jurnal pendidikan tuntas, and reasonable efforts should be made to remove all references to this article. Article information: this article Retracted Augustus 16 2024.